How can public expenditure improve households' sanitation behavior? - Nair J., Krishna,Mishra, Pulak,Rahut, Dil Bahadur (Asian Development Bank Institute, 2023)
The social impact of sanitation is multifaceted. It has repercussions for health, education, and the local environment, as well as overall human development and economic growth. Unsafe sanitation poses environmental and health risks. In light of the health hazards, the Government of India has introduced the Swachh Bharat Mission (SBM) to improve sanitation conditions. This paper investigates how the Swachh Bharat Mission (SBM), as a public-funded initiative of the Government of India, can improve the sanitation environment in different states. The paper also explores whether the SBM has been successful as a catalyst in improving the sanitation infrastructure and ensuring its long-term sustainability. [...]
10.56506/IKTC7428
Keywords: Graue Literatur; sanitation environment; public expenditure; Swachh Bharat Mission; India